2021
DOI: 10.12737/1998-0744-2021-9-2-41-47
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of Pedagogical Communication in the E-Learning of the Mathematical Disciplines

Abstract: In the current sanitary and epidemiological situation and the total transition to a distance format of communication between the teacher and the student, the problem of maintaining the quality of the educational services provided at the proper level becomes especially urgent. One of the options for solving this problem is seen by the authors in a well-established feedback loop with students and a competent organization of pedagogical communication within the framework of e-learning. This article describes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Surveys before the elections showed that more than 40 per cent of voters wanted her to continue as Prime Minister, while only 10-12 per cent supported her party. Among voters of the Independence Party and the Progressive Party, support for Jakobsdóttir as Prime Minister was similar or greater than the support for their respective party leaders, Bjarni Benediktsson and Sigurður Ingi Jóhannsson (Kjarninn 2021b, Maskína 2021.…”
Section: Cabinet Reportmentioning
confidence: 99%
“…Surveys before the elections showed that more than 40 per cent of voters wanted her to continue as Prime Minister, while only 10-12 per cent supported her party. Among voters of the Independence Party and the Progressive Party, support for Jakobsdóttir as Prime Minister was similar or greater than the support for their respective party leaders, Bjarni Benediktsson and Sigurður Ingi Jóhannsson (Kjarninn 2021b, Maskína 2021.…”
Section: Cabinet Reportmentioning
confidence: 99%